2014
DOI: 10.3138/cjpe.29.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Knowledge Translation Through Evaluation: Evaluator as Knowledge Broker

Abstract: Th e evaluation literature has focused on the evaluation of knowledge translation activities, but to date there is little, if any, record of attempts to use evaluation in support of knowledge translation. Th is study sought to answer the question: How can an evaluation be designed to facilitate knowledge translation? A single prospective case study design was employed. An evaluation of a memory clinic within a primary care setting in Ontario, Canada, served as the case. Th ree data sources were used: an evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
0
16
0
3
Order By: Relevance
“…The bulletins, therefore, are also a "knowledge brokering" activity. They provide an opportunity for synthesizing knowledge for use in practice (Donnelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulletins, therefore, are also a "knowledge brokering" activity. They provide an opportunity for synthesizing knowledge for use in practice (Donnelly et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This article seeks to answer the question, How can information about monitoring, evaluation, and lessons learned be available when critical programming decisions need to be made or when tools for advocacy are required? Donnelly, Letts, Klinger, and Shulha (2014) found that although the field of evaluation has been focused on use of evaluation, there is minimal literature on how evaluation can support knowledge translation and how knowledge translation can support evaluation use. This article addresses this gap by sharing a case example of how The Fred Hollows Foundation's Indigenous Australia Program used knowledge-translation theory to enhance the uptake of monitoring, evaluation, and learning information.…”
Section: Key Pointsmentioning
confidence: 99%
“…A utilização do termo na área da saúde surgiu timidamente em meados da década de 1970 e começou a ser amplamente usado a partir da década de 1990 (DAVISON, 2009;DONNELLY, 2014 Davison (2009) identificou, dentre diversas definições sobre translação do conhecimento, três que julga mais importantes: (1) a troca, síntese e aplicação ética por meio de um sistema complexo de interação entre pesquisadores e usuários; (2) a troca, síntese e comunicação efetiva dos achados relevantes e confiáveis; e (3) a revisão, estudo, identificação e aplicação prática da pesquisa de qualidade pelos stakeholders.…”
Section: Translação Do Conhecimentounclassified
“…Além disso, transforma a avaliação em um mecanismo para traduzir o conhecimento em prática (DONNELY ET AL., 2014). Donnelly et al (2014) realizaram uma avaliação de abordagem participativa numa clínica de atenção primária em Ontário, Canadá, com o objetivo de verificar de que modo a translação do conhecimento foi estimulada e qual foi o papel do avaliador nesse processo. Para os autores, é importante tanto a participação dos stakeholders como do avaliador, ou seja, dos atores intermediá-rios.…”
Section: Translação Do Conhecimentounclassified
“…These reports are useful in providing a framework for the daily practice of a KB in public health and primary care settings, including a description of the specific tasks performed within different clinical contexts. KB roles that were common across several reports (8,13,15,17,19,21,(24)(25)(26) included engagement with stakeholders through site visits and in-person communication. Although literature suggests that KT strategies involving face-to-face communication with end-users may be more successful for relationship building and promoting HCP practice change (8,17), this approach can be costly and resource intensive (18), and thus not feasible.…”
Section: Introductionmentioning
confidence: 99%